2012
DOI: 10.1080/13546805.2011.569372
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study exploring the contribution of working memory to “jumping to conclusions” in people with first episode psychosis

Abstract: This study casts doubt on reduced global WM as an explanation of JTC. Rather it may be that the differences in reasoning are related to the manipulation of visual material and do not extend to other areas of neuropsychological functioning. However, as our sample is small it may be underpowered to detect important differences. Future work is therefore needed to replicate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 39 publications
1
19
0
2
Order By: Relevance
“…They were able to replicate the well-established finding that patients with schizophrenia drew less information during decision making compared to controls, but that ketamine had no effect on performance. The results of longitudinal studies in patients are somewhat mixed: in people with long-term illness the information gathering style (accessed either as DTD or JTC) remains stable [36], [37], while in people with early psychosis there has been found a decrease of information sampling in one study [38] and increase in the two others [39], [40]. The latter study had the longest follow up period (2 years) and found that less hasty decision makers were also less symptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…They were able to replicate the well-established finding that patients with schizophrenia drew less information during decision making compared to controls, but that ketamine had no effect on performance. The results of longitudinal studies in patients are somewhat mixed: in people with long-term illness the information gathering style (accessed either as DTD or JTC) remains stable [36], [37], while in people with early psychosis there has been found a decrease of information sampling in one study [38] and increase in the two others [39], [40]. The latter study had the longest follow up period (2 years) and found that less hasty decision makers were also less symptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work with patients with more chronic difficulties indicated that hasty decision‐making would likely persist (Peters & Garety, ; So et al ., ). Findings from this study are consistent with research with first‐episode service users (Menon et al ., ; Ormrod et al ., ; Woodward et al ., ), which indicates ‘JTC’ is changeable.…”
Section: Discussionmentioning
confidence: 99%
“…Although this number is too small to draw any conclusions, it would suggest 'JTC' may not be stable over time. Ormrod et al (2012) investigated stability of JTC in people with first-episode psychosis. When tested over two time points around 8 months apart at baseline, 17/29 demonstrated JTC, whereas at follow-up this was 9/29 indicating a degree of instability in JTC over time.…”
mentioning
confidence: 99%
“…Given the similar findings of the large studies of and Falcone (2013), we can now be confident of an association of JTC with working memory. Arguably, studies such as that of Ormrod et al (2012) failed to find such an association because of a small sample size. The working memory impairment was associated with levels of current intellectual functioning (and these were not separable predictors of JTC).…”
Section: Discussionmentioning
confidence: 99%
“…Woodward et al 2008), including a study indicating that data gathering may improve when memory load in the beads task is reduced (Menon et al 2006). However, a study with 29 patients with early psychosis did not find a significant association of JTC with verbal working memory (Ormrod et al 2012). Given the results of the largest studies, there are increasing grounds to believe that working memory limitations contribute to the presence of JTC.…”
Section: Introductionmentioning
confidence: 99%